First-order allpass network using CFTA - Torteanchai, Usa; Kumngern, Montree (My University, 2014)
This paper presents a new current-mode first-order allpass network. The network employs only one current follower transconductance amplifier, one capacitor and two resistors. Unlike previously works, the proposed network offers both non-inverting and inverting allpass transfer functions into one circuit. Moreover, the current gain of the network can be adjusted. The output terminal of the filter possesses high impedance level which is directly connected to the next stage without any buffer circuit. For realizing allpass transfer functions, no component-matching conditions are required. The simulation results are also used to verify the workability of the proposed network. © 2014 IEEE.
Keywords: current follower transconductance amplifier; current-mode circuit; first-order allpass network